Propagation Characteristics of SH Wave in Orthotropic Layer/Piezoelectric Column Structure. Issue 1 (1st December 2022) - Li, TaiSong; Wang, YanHong
Abstract: The propagation characteristics of SH waves along the circumferential direction in an orthotropic layer/piezoelectric column structure with a non-ideal interface are studied in this paper. By solving the governing equations, the solutions to the problem are expressed by the first and second Bessel functions. The dispersion equation is obtained by the boundary conditions and the interface conditions. The numerical examples are provided to show the effects of the degree of orthogonal anisotropy, the thickness-diameter ratio, and the imperfect interface on the dispersion characteristics.